Outcomes of Foreign Body Inhalation in A Tertiary Care Hospital - Hussain, Muhammad Saddam; Hussain, Muhammad Behram; Zaib, Kanwal; Baig, Muhammad Ashfaq; Habib, Faisal (Biological and Clinical Sciences Research Journal, 2025)
Foreign body inhalation (FBI) is a potentially life-threatening emergency, particularly in children, and is associated with significant morbidity if diagnosis and management are delayed. Objective: To evaluate the clinical presentation, diagnostic findings, management, and outcomes of foreign body inhalation among children presenting to a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the Department of Paediatric Medicine, Benazir Bhutto Hospital, Rawalpindi, from January 2025 to April 2025. A total of 103 children aged 3–12 years with suspected foreign body inhalation were enrolled using non-probability consecutive sampling. Clinical features, radiological findings, bronchoscopic outcomes, and follow-up results were recorded on a standardized pro forma. Results: The mean age of patients was 6.1 ± 2.3 years, with the majority aged 3–6 years (56.3%). Male predominance was noted (59.2%). The most common presenting symptoms were coughing (79.6%), wheezing (65.0%), and choking (53.4%). Chest X-ray abnormalities were detected in 69.9% of cases, and rigid bronchoscopy confirmed foreign bodies in 93.2% of these cases. The right main bronchus was the most frequent site of impaction (45.6%). Organic foreign bodies, predominantly peanuts and seeds, accounted for 68.9% of cases. Bronchoscopic removal was successful in 91.3% of cases on the first attempt, while repeat procedures were required in 8.7% of cases. Complications included post-bronchoscopy pneumonia (11.7%) and atelectasis (7.8%). Conclusion: Foreign body inhalation is most common among younger children, with organic materials being the predominant cause. Timely diagnosis and prompt bronchoscopy result in excellent outcomes with minimal complications.